Landscape evaluation of the “Sheikh Sou” suburban park created in an old Mediterranean rangeland - Chouvardas D.; Sidiropoulou A.; Atskakani M.; Papadimitriou M.; Sklavou P.; Karatasiou M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Rangelands in the Mediterranean region are diverse ecosystems holding great recreation potentials. Landscape evaluation is recognized as a powerful and interdisciplinary research method for evaluating diverse landscape systems such as natural parks and suburban recreation areas. The “Sheikh Sou” suburban park, which is located on the northern edge of the Thessaloniki metropolitan area in North Greece, was chosen as the study area. Sheikh Sou, originally a typical Mediterranean rangeland, was partially restored by planting pine trees in the mid 30’s as an erosion prevention strategy. Following a long history of disturbances, today the park contains six vegetation types: old pine groves, shrublands, grasslands, mixed shrublands with pines that have emerged after a fire due to natural revegetation and several riparian zones. All these vegetation types form a rich mosaic of landscape units that this paper aimed to evaluate. For this purpose, twenty landscape evaluation criteria were applied and graded by experts and a visual management goal was set. The analysis showed that mixed shrublands and riparian areas were visually attractive landscapes receiving higher grades, followed by grasslands. As opposed to this, shrublands and old pine groves received lower grades and became less sensitive to management interventions. Our results suggest that pine groves and ungrazed shrublands had a negative effect on total landscape value.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)